Alocação de custos indiretos de uma estrutura de vendas compartilhada: um caso aplicado - Yarussi, Fernando Modesto (2013)
The objective of this study is to verify, by means of action research, how to establish criteria to ensure the correct and proper allocation of selling costs, providing transparency in the technical aspects of the distribution of costs. Additionally aims to meet the expectations of internal users, featured by controller of business areas. This research was developed in a multinational company, from electric and electronic sector, which makes use of a shared organizational structure Sales. The data collection was performed using semi-structured interviews in order to identify the necessary elements to input for a framework that would meet the requirements of internal users. Based on the literature and information of these users, the results provided the elaboration of a method of cost allocation aiming to supply an immediate demand of the studied company.